2009
DOI: 10.1097/rli.0b013e3181a24512
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Enhancement in Early Dynamic Liver MR Imaging in an Animal Model: Comparison of Two Injection Regimen and Two Different Doses Gd-EOB-DTPA (Gadoxetic Acid) With Standard Gd-DTPA

Abstract: Despite the lower amount of gadolinium in the standard dose of Gd-EOB-DTPA, the results showed that the arterial enhancement in Gd-EOB-DTPA-enhanced dynamic liver MRI was comparable to Gd-DTPA. This result can be explained mainly by the higher relaxivity. Choosing a lower injection rate additionally supported to compensate for the lower injection volume by stretching the bolus without decreasing the peak. In this respect, an injection rate of 1 mL/s showed better results with regard to the arterial enhancement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
73
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(75 citation statements)
references
References 25 publications
0
73
1
1
Order By: Relevance
“…Other institutions administer it with a slower injection rate of 1 ml/s to spread the contrast bolus, thereby reducing the risk of a poorly timed arterial phase [6,10,11,13,25]. Dilution of gadoxetate disodium with saline is an alternative approach to spread the contrast bolus [9].…”
Section: Influence Of Contrast Injection Ratementioning
confidence: 99%
“…Other institutions administer it with a slower injection rate of 1 ml/s to spread the contrast bolus, thereby reducing the risk of a poorly timed arterial phase [6,10,11,13,25]. Dilution of gadoxetate disodium with saline is an alternative approach to spread the contrast bolus [9].…”
Section: Influence Of Contrast Injection Ratementioning
confidence: 99%
“…10 A recent study revealed that use of a slow injection rate (one mL/s) can facilitate equivalent arterial enhancements between gadoxetic acid and extracellular GBCAs. 11 Currently, no published data compare enhancement of liver lesions on arterial phase images enhanced by gadoxetic acid and extracellular GBCAs. In our experience, however, the 2 agents provide visually equivalent enhancements.…”
Section: Magnetic Resonance In Medical Sciencesmentioning
confidence: 99%
“…Recently, a new MRI contrast medium-gadoxetic acid or Gd-EOB-DTPA (Primovist, Bayer Schering Pharma, Berlin, Germany)-with the properties of both extracellular gadolinium chelate and a liver-specific (hepatocyte-targeting) contrast agent has become available. A bolus injection of gadoxetic acid enables the assessment of tumor vascularity on arterial-phase images as well as a functional hepatic (i.e., hepatocyte-phase) images (8,9). The hepatocyte-phase assessments can be performed approximately 20 min after administration of the contrast agent, when approximately 50% of the agent has been taken up by the hepatocytes (10)(11)(12).…”
mentioning
confidence: 99%